Influenza A Virus Pre-Infection Exacerbates Pseudomonas aeruginosa-Mediated Lung Damage Through Increased MMP-9 Expression, Decreased Elafin Production and Tissue Resilience - Villeret, Berengère; Solhonne, Brigitte; Straube, Marjolène; Lemaire, Flora; Cazes, Aurélie; Garcia-Verdugo, Ignacio; Sallenave, Jean-Michel (Frontiers in Immunology, 2020)
Individuals with impaired immune responses, such as ventilated and cystic fibrosis patients are often infected with Pseudomonas aeruginosa (P.a) bacteria, and a co-infection with the Influenza virus (IAV) is often present. It has been known for many years that infection with IAV predisposes the host to secondary bacterial infections (such as Streptococcus pneumoniae or Staphylococcus aureus), and there is an abundance of mechanistic studies, including those studying the role of desensitization of TLR signaling, type I IFN- mediated impairment of neutrophil chemokines and antimicrobial production, attenuation of IL1β production etc., showing this. However, little is known about the mechanistic events underlying the potential deleterious synergy between Influenza and P.a co-infections. We demonstrate here in vitro in epithelial cells and in vivo in three independent models (two involving mice given IAV +/– P.a, and one involving mice given IAV +/– IL-1β) that IAV promotes secondary P.a-mediated lung disease or augmented IL-1β-mediated inflammation. We show that IAV-P.a-mediated deleterious responses includes increased matrix metalloprotease (MMP) activity, and MMP-9 in particular, and that the use of the MMP inhibitor improves lung resilience. Furthermore, we show that IAV post-transcriptionally inhibits the antimicrobial/anti-protease molecule elafin/trappin-2, which we have shown previously to be anti-inflammatory and to protect the host against maladaptive neutrophilic inflammation in P.a infections. Our work highlights the capacity of IAV to promote further P.a-mediated lung damage, not necessarily through its interference with host resistance to the bacterium, but by down-regulating tissue resilience to lung inflammation instead. Our study therefore suggests that restoring tissue resilience in clinical settings where IAV/P.a co-exists could prove a fruitful strategy.